2015
DOI: 10.1002/bimj.201400108
|View full text |Cite
|
Sign up to set email alerts
|

Model averaging quantiles from data censored by a limit of detection

Abstract: In chemical risk assessment, it is important to determine the quantiles of the distribution of concentration data. The selection of an appropriate distribution and the estimation of particular quantiles of interest are largely hindered by the omnipresence of observations below the limit of detection, leading to left-censored data. The log-normal distribution is a common choice, but this distribution is not the only possibility and alternatives should be considered as well. Here, we focus on several distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…A simulation study shows that the proposed test has good properties in terms of both Type I error rate and power. Nysen et al (2016) discuss how to derive estimates for quantiles of interest in a chemical risk assessment study, when the observed (say continuous) distribution suffers from the presence of a spike at zero. These authors discuss cases where this spike is associated to left-censored data, that is to data below the limit of detection.…”
mentioning
confidence: 99%
“…A simulation study shows that the proposed test has good properties in terms of both Type I error rate and power. Nysen et al (2016) discuss how to derive estimates for quantiles of interest in a chemical risk assessment study, when the observed (say continuous) distribution suffers from the presence of a spike at zero. These authors discuss cases where this spike is associated to left-censored data, that is to data below the limit of detection.…”
mentioning
confidence: 99%